Ammoniacal Nitrogen Contaminant in Water of Kaliori Landfill Area in Banyumas - Sri Royani; Adita Silvia Fitriana (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Kaliori Landfill is one of the inactive landfills in Banyumas Regency. The presence of garbage and a full leachate pond in the area is feared to pollute the waters around the landfill. One of the water quality parameters is ammoniacal nitrogen (NH3-N) based on Government Regulation of the Republic of Indonesia Number 82 in 2001. The aim of this research was to find the quality of water in landfill area based on ammoniacal nitrogen parameter. The water studied was one sample of leachate, two samples of river water and five samples of ground water in the landfill area with a radius less than 1 kilometers. Spectrophotometry method was used to find NH3-N concentration. Based on the test results, leachate and ground water have reach ammoniacal nitrogen quality standard, there were <2.0 mg/L and <0.5 mg/L respectively. Meanwhile, the ammoniacal nitrogen in river water was >2.5 mg/L, they have exceeded the established quality standards.